Binding Lalava: Unravelling the Functionality of Pattern - Latu, Vena (Auckland University of Technology, 2022)
Lalava is a form of Tongan construction that consists of lashing two lines of kafa (sennit), a braided rope made from the inner fibres of the coconut husks; the lines intersect one another repeatedly, circling up and down to form geometric patterns as it binds and connects two or more beings and objects. In contemporary contexts, lalava is considered more as an art form rather than a method developed by ancient Tongans and Oceanians to bind large structures such as the fale (house) and vaka (canoe). While it is evident that lalava is used as a decorative element expressing ancient Tongan narratives and metaphors, this research project, investigates the functionality of lalava to consider how it contributes to maintaining structural stability.